Use of AgomiR and AntagomiR technologies to alter satellite cell proliferation in vitro, miRNA expression, and muscle fiber hypertrophy in intrauterine growth-restricted lambs - Greene, M. A.; Worley, G. A.; Udoka, A. N. S.; Powell, R. R.; Bruce, T.; Klotz, J. L.; Bridges, W. C.; Duckett, S. K. (Frontiers in Molecular Biosciences, 2023)
Introduction: microRNAs (miRNAs) are small non-coding RNAs that work at the posttranscriptional level to repress gene expression. Several miRNAs are preferentially expressed in skeletal muscle and participate in myogenesis. This research was conducted to alter endogenous miRNA expression in skeletal muscle to promote muscle hypertrophy. Methods: Two experiments were conducted using mimic/agomiR or antagomir technologies to alter miRNA expression and examine changes in myoblast proliferation in vitro (experiment 1) and muscle hypertrophy in vivo (experiment 2). In vitro experiments found that antagomiR-22-3p and mimic-127 increased myoblast proliferation compared to other miRNA treatments or controls. These miRNA treatments, antagomiR-22-3p (ANT22) and agomiR-127 (AGO127), were then used for intramuscular injections in longissimus muscle. Results and discussion: The use of antagomiR or mimic/agomiR treatments down-regulated or up-regulated, respectively, miRNA expression for that miRNA of interest. Expression of predicted target KIF3B mRNA for miR-127 was up-regulated and ACVR2a mRNA was up-regulated for miR-22-3p. ANT22 injection also up-regulated the major regulator of protein synthesis (mTOR). Proteomic analyses identified 11 proteins for AGO127 and 9 proteins for ANT22 that were differentially expressed. Muscle fiber type and cross-sectional area were altered for ANT22 treatments to transition fibers to a more oxidative state. The use of agomiR and antagomir technologies allows us to alter miRNA expression in vitro and in vivo to enhance myoblast proliferation and alter muscle fiber hypertrophy in IUGR lambs during early postnatal growth.